Numerical Assessments on Flow Topology and Heat Transfer Behavior in a Round Tube Inserted with Three Sets of V-Ribs - Amnart Boonloi; Withada Jedsadaratanachai (Frontiers in Heat and Mass Transfer, 2023)
Simulation of fluid-flow topology and thermal behavior in a round tube heat exchanger (RTHX) installed by three V-rib sets is reported. The expected phenomena for the rib installation are the generated vortex flow, impinging flow, greater fluid blending and thermal boundary layer disturbance (TBLD). These phenomena are key causes of the augmentation of heat transfer potentiality and thermal efficiency of the RTHX. Effects of rib height (b1 = 0.05D – 0.25D and b2 = 0.05D – 0.25D), rib pitch or rib spacing (P = D, 1.5D and 2D) and fluid directions (positive x (+x flow direction) and negative x (–x flow direction)) on fluid-flow behavior and thermo-hydraulic characteristic are considered. The laminar air flow under Reynolds numbers between 100 to 2000 calculated by the inlet condition is focused. The current-numerical problem of the RTHX fitted with V-ribs can be solved by a commercial code/program (the finite volume analysis). Firstly, the tested-tube model is carefully validated. The preliminary results of the validation show that the numerical model has great consistency for fluid flow and thermal structure prediction. The simulated outcomes are plotted in features of streamlines flow, local Nusselt number contours and temperature contours which explains the mechanism within the RTHX. The thermal assessments within the RTHX are performed with dimensionless variables, which include the Nusselt number, the friction factor and the thermal enhancement factor. The important mechanisms: vortex flow, impinging flow, better fluid blending and TBLD, are observed when the RTHX are installed with ribs. The maximum heat transfer potentiality is 19 times upper than that of the RTHX without ribs and the optimum thermal enhancement factor is around 4.10.
Keywords: Heat Transfer Mechanisms; Fluid Dynamics and Turbulent Flows; Heat transfer and supercritical fluids